Implementation of Lean Manufacturing Approach Using Value Stream Mapping to Optimize Cycle Time and Reduce Process Waste (Case Study: CV. Teguh Jaya Mandiri) - Maknun, Salmaa Lu'lu'ul; Aidil, Joumil (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Competition in several service sector companies and the manufacturing industry is getting tighter, which requires service companies as well as manufacturing to increase their production. Solving this problem can be started by improving the company system. Especially in minimizing or eliminating waste from the production process. CV. Teguh Jaya Mandiri is a company engaged in packaging screen printing services, its current condition has obstacles in the processing period that exceeds the time limit and does not match consumer demand. This is because the company has not done a good analysis in calculating the cycle time that occurs during the entire process. Thus, researchers can identify the level of waste and proposed improvements to optimize cycle time and reduce waste in the production process. In this research, the lean manufacturing method is used with the Value Stream Mapping tool followed by Process Activity Mapping which is one of VALSAT (Value Stream Analysis Tools). The results showed that Process Activity Mapping using the Value Stream Mapping approach identified waste in the production process at CV. Teguh Jaya Mandiri, namely there are overprocesses. The weighting result of overprocesses is 0,21. Cycle Time has decreased from 24812,5 seconds to 13908,5 seconds or 3 hours 52 minutes by eliminating NVA and reducing existing VA.